Factors Affecting Online Purchase Intentions of Consumers in the Cosmetic Industry - *Sahar Raees; Syed Muddasir Hussain; Zeeshan Malik (Review Journal of Social Psychology & Social Works, 2025)
Studies regarding online buying intentions require a deeper investigation because the cosmetics industry continues to expand rapidly as online shopping popularity rises. This research examines the impact of three factors namely user interface design and ease of use and social media marketing on customers' purchasing intentions for online cosmetics products. Consumer behavior modification results primarily from two social media forces: influencer support and interactive content delivery specifically through Instagram and TikTok platforms. Simple navigation together with effortless transaction procedures in e-commerce systems create substantial influence on customer satisfaction and selection behavior. To keep online customers the user interface must achieve functional perfection without sacrificing visual attractiveness. The analysis provides critical details about improving online sales performance and digital marketing method at cosmetic companies through analyzing these variables. The results present specific steps companies can use to enhance website functionality as well as optimize social media promotion methods and design better interfaces that satisfy consumer needs.